Experimental and theoretical band alignment study of MPS3 (M = Mn, Fe, Co, Ni) for designing tailored 2D heterostructures - Dominika Majchrzak; Miłosz Rybak; Rafał Bartoszewicz; Jan Plutnar; Umer Ahsan; Miłosz Grodzicki; Detlef Hommel; Magdalena Birowska; Zdeněk Sofer; Robert Kudrawiec (npj 2D Materials and Applications)
Abstract Van der Waals crystals offer opportunities to engineer material properties by stacking diverse 2D layers into heterostructures. Charge redistribution at these interfaces, governed by band alignment and Fermi levels, enables control over optical, electronic, and magnetic behavior. In this study, we investigated the band alignment and excitation spectra of exfoliated MPS3 (M = Mn, Fe, Co, Ni) using X-ray and UV photoelectron spectroscopy, optical absorption, and DFT + U calculations. Ionization potentials from 5.4 eV (FePS3) to 6.2 eV (NiPS3) were determined. The resulting band diagrams differentiate localized d states from hybridized p-d states, offering insights for designing functional heterostructures. Selective occupation of unoccupied 3d states provides a pathway to tune magnetic order. Theoretical results show that MnPS3 is well-aligned for both hydrogen and oxygen evolution reactions (HER and OER), while other MPS3 are promising for OER. MnPS3/NiPS3 heterostructure exhibits optimal band alignment for efficient water splitting across a broad pH range.